Your transforming role in preventative healthcare. Issue 5 (3rd May 2020) - Helps, John
Abstract : ABSTRACT: Veterinary nurses can play a key role in preventative healthcare and this should be highlighted to clients and veterinary surgeons during VN Awareness Month. In collaboration with University of Nottingham's Centre for Evidence-based Veterinary Medicine, MSD Animal Health's Keeping Britain's Pets Healthy initiative was launched. The project revealed that neither owners nor veterinary surgeons were completely confident about what services veterinary nurses could provide. As the veterinary nursing title is not protected in the UK it is not possible to determine how many of the staff described as "veterinary nurses" were actually registered veterinary nurses. A key conclusion is that there is an urgent need for further understanding and clarity of the roles and responsibilities of nurses within small animal practices. The two-year project resulted in guidelines being created for practices to consider throughout the preventative healthcare experience of clients. An important key theme identified was the role that veterinary nurses and receptionists play in educating and engaging clients in preventative healthcare.